2004
DOI: 10.1080/10717540490494087
|View full text |Cite
|
Sign up to set email alerts
|

Design and Study of Rifampicin Oral Controlled Release Formulations

Abstract: Oral controlled release formulations of rifampicin have been developed by using hydroxypropyl methylcellulose polymer at different ratios. From in vitro release data, we found that the release was extended with an increase of polymer proportion from 20% to 40%. However, increase in polymer beyond 40% resulted in no significant change in the release rate. There was a distinct difference in the release rate and release character due to variation in the compression force. The release kinetics were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…10,11 Furthermore, repeated oral administration of high RIF doses yields autoinduction of RIF's own metabolism leading to a decrease in its bioavailability. 12 An alternative, a more effective approach to treat pulmonary TB is to deliver drugs directly to the lungs to achieve high local drug concentration for extended duration. Also, depending on the physicochemical characteristics of the particular drug and the formulation, pulmonary delivery could also result in systemic bioavailability of the drug, if treatment of extrapulmonary TB is desired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Furthermore, repeated oral administration of high RIF doses yields autoinduction of RIF's own metabolism leading to a decrease in its bioavailability. 12 An alternative, a more effective approach to treat pulmonary TB is to deliver drugs directly to the lungs to achieve high local drug concentration for extended duration. Also, depending on the physicochemical characteristics of the particular drug and the formulation, pulmonary delivery could also result in systemic bioavailability of the drug, if treatment of extrapulmonary TB is desired.…”
Section: Introductionmentioning
confidence: 99%
“…This is a potentially easy solution since RIF is an inexpensive drug and well-known among physicians worldwide . However, this approach has the potential to increase unwanted side effects such as hepatotoxicity. , Furthermore, repeated oral administration of high RIF doses yields autoinduction of RIF’s own metabolism leading to a decrease in its bioavailability …”
Section: Introductionmentioning
confidence: 99%
“…This is a part of research efforts from author's lab on the development of oral controlled release formulations of anti-tubercular drugs rifampicin and isoniazid. In this regard, authors have reported the oral CR formulations of rifampicin (20)(21) and rifampicin and isoniazid combination (22). In light of the above discussion, the objective of this study was to formulate controlled release oral tablet formulations of isoniazid by matrix embedding technique using HPMC polymer of different viscosity grades as a retardant material.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, four different sustained release tablet formulations with same weighted tablets were developed to determine optimum formulation using different polymers which are Carbopol 974P, HPMC K100M, PEO (Polyox WSR303), guar gum (Supercol NF) and alginate (Protanal LF240). The polymer concentration was fixed to 40 % (w/w) according to previous studies (22). Because of the commercial tablet contains 75 mg venlafaxine, our tablet formulations contain 84.85 mg (VH) which is equivalent to 75 mg venlafaxine free base.…”
Section: Preparation Of Formulationsmentioning
confidence: 99%